Strategic Questioning in EFL Classrooms: A Closer Look at Higher-Order, Factual, Probing, and Divergent Questions - Aeni, Nur; Amra Ariyani (Eduvelop: Journal of English Education and Development, 2025)
This study aimed to investigate how English teachers' questioning techniques affected their students' cognitive growth and engagement. The study aimed to determine the kinds of questions that English teachers employ when instructing their students. Classroom observations and semi-structured interviews with two instructors and twenty students from SMP Negeri 49 Makassar were among the qualitative approaches used in the study. The results showed that both professors used various questioning techniques, such as factual, higher-order, divergent, and probing questions. Divergent questions promoted creative thinking by permitting numerous responses, whereas probing questions prompted students to consider more deeply and elaborate on their solutions. This study's importance stems from its ability to shed light on the function of questioning techniques in EFL classes. The study also offers practical implications for improving teaching practices and student learning outcomes. Future research could explore the impact of questioning strategies across different educational contexts and learning levels and their long-term effects on students’ academic performance. This study contributes to the growing body of research on questioning strategies in EFL classrooms, providing valuable insights into how questioning methods can improve student engagement and cognitive development. It also offers practical recommendations for educators to optimize questioning techniques to enhance teaching effectiveness.